Microbe Goes to School: Implementation of Experiential Learning for Students of SMAN 5 Tanjungpinang - Oprasmani, Elfa; Amelia, Trisna; Nevrita; Asikin, Nurul; Sumarni, Een (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
One of the problems faced by the partner at SMA Negeri 5 Tanjungpinang is the low learning interest of students in biology lessons and the lack of student literacy about the role of microorganisms in life. Learning with an experiential learning approach in biology lessons can be a solution. Experiential learning is conducted in two stages, namely face-to-face in the classroom and Open Lab. The PKM activity is followed by 42 students who are tested with pre-tests and post-tests. The results are analyzed using N-Gain. The PKM program shows success in increasing students' learning interest and achieving literacy about the role of bacteria in life. The increase in students' learning interest falls into the moderate category, with an average N-Gain score of 0.43 (increase 43%). This is because the advantage of the PKM program through the application of experiential learning in biology involves direct real-world experience and active participation, often through laboratory work, to deepen understanding and acquire practical skills for students. The weakness of this PKM activity is that it is only carried out incidentally; therefore, for the sustainability of this program, it needs to be implemented systematically to improve students' interest and literacy, especially about the role of microorganisms.